Disease Incidence and Severity of Spot Blotch in Different Dates of Sowing of Wheat Crop (Triticum aestivum L.) - Pant , Yamini; Pokhrel, Chandra Prasad (Journal of Plant Resources, 2024)
Spot blotch disease, Bipolaris sorokiniana, has become a very enduring disease of wheat crops in Nepal and elsewhere. The study aimed to identify the severity of spot blotch disease and its consequence in two different showing dates (timely sowing and late sowing) of wheat crop. A field experiment was conducted in Bhatkepati, Kirtipur, Middle Hill, Nepal, and the experiment plots with the size of 10 x 22 m were laid out with three replications. Five plots of 1 m2 were set from each experiment plot for data collection. The study result showed a significant impact of spot blotch on the area under the disease progress curve yield, thousand kernel weight, spike length, grains per spike and plant height. The disease severity and area under the disease progress curve on the timely sowing wheat crop were 31.3% and 878.9, respectively, whereas the values of disease severity and area under the disease progress curve on the late sowing crop were 44.9% and 1321.1 respectively. The yields of timely sowing and late sowing wheat crops were 415.7 gm and 328.7 gm/m2, respectively, whereas the thousand kernel weight was 48.7 gm and 45.0 gm, respectively. Similarly, spike length, plant height and grains per spike were significantly high in the timely sowing wheat crop. The late sowing date can increase the disease severity in the wheat crop, thereby significantly affecting yield and productivity.